2015
DOI: 10.1007/s10661-014-4256-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and residue of pymetrozine in rice field ecosystem

Abstract: The dissipation and residue of pymetrozine in rice field ecosystem were studied based on a novel and reliable analytical method for pymetrozine in paddy water, soil, rice straw, brown rice, and rice husk. The pymetrozine residues were extracted with acetonitrile and cleaned up by Carb-NH 2 SPE cartridge and determined by high-performance liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS-MS). The dissipation of pymetrozine followed first-order kinetics and its half-lives ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
0
22
2
Order By: Relevance
“…Rice ( Oryza sativa L.) is the most important grain and widely cultivated in China [1,2,3,4]. Thus, the quality and safety of rice are highly related to human health and national strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Rice ( Oryza sativa L.) is the most important grain and widely cultivated in China [1,2,3,4]. Thus, the quality and safety of rice are highly related to human health and national strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, pymetrozine residues could be extracted from samples using acetonitrile (Dias et al, ; Jang et al, ; Zhang et al, ). For example, Jang et al found that methyl cyanide (MeCN) is a better exaction solvent for pymetrozine in pepper than ethyl acetate (EtOAc).…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports, pymetrozine residues could be extracted from samples using acetonitrile (Dias et al, 2013;Jang et al, 2014;Zhang et al, 2015). Garrido-Frenich, 2016; Walorczyk & Drożdżynski, 2012).…”
Section: Extraction and Purificationmentioning
confidence: 99%
See 2 more Smart Citations